PENGARUH DISIPLIN TERHADAP PRESTASI KERJA PEGAWAI DI DINAS SOSIAL KABUPATEN HALMAHERA BARAT - Kurang, Olisstefiyani; Ogotan, Martha; Dengo, Salmin (Sam Ratulangi University, 2016)
ABSTRACT: Although the discipline rules of civil servent is dearly and distinct define the obligations andprobubitions, but the fact shows that there still a lot of discipline violations done by the civil servent. The purpose ofthis research is to find out the influence of discipline on employee?s work achievement of the social services indistrict of West Halmahera. The type of this research is exploratory research with quantitative approach. Theresearch sample are 35 respondents drawn by random at the social services in district of west Halmahera. For thedata collection used questionnaire and interview technique.The data analysis tehniques used statistic analysis of linear reqression and product moment correlation.Based on the data analysis is thengwen coclusions as follows : (1). The discipline has a funcional relationship orpositive influence and significant as wel as shape or linear pattern on employee?s work achievement of the socialservices in district of west Halmahera. That, the increasing of the work achievement. (2). The discipline has acorrelation and the significant determination forwards the development on employee?s work achievement of thesocial services in district of west Halmahera.That, the more discipline, the more it gets achievement. Based on the conclusions is then developed somesuggestions as follows : (a). The preventive discipline needs to be improved on employee?s of the social services indistrict of west Halmahera. For that, the coaching of discipline is necessary to do continuously. (b). The repressivediscipline needs to applying for the employee?s who violate the rules of discipline. For that the punishment ofdiscipline should be done consistenly.Keyword : Discipline, work achievement